Immunomodulatory therapies for COVID-19 - Mathur, Poonam; Kottilil, Shyamasundaran (Frontiers in Medicine, 2022)
Purpose. As COVID-19 disease progresses, the host inflammatory response contributes to hypoxemia and severe and critical illness. In these latter stages of disease, patients may benefit from immunomodulatory therapies to control the aberrant host inflammatory response. In this review, we provide an overview of these therapies and provide summaries of the studies that led to issuance of FDA Emergency Use Authorization or recommendation by the Infectious Diseases Society of America (IDSA). Methods. We reviewed English-language studies, Emergency Use Authorizations (EUAs), and guidelines from March 2020 to present. Conclusions and Relevance. There are several therapies with proposed benefit in severe and critical COVID-19 disease. Few have been issued FDA EUA or recommendation by the Infectious Diseases Society of America (IDSA). Physicians should be familiar with the evidence supporting use of these therapies and the patient populations most likely to benefit from each.